FOREIGN EXPERIENCE IN PREVENTING AND COMBATING CORRUPTION IN PROSECUTORIAL OFFICES AND WAYS OF IMPLEMENTING IT IN UKRAINE (Bulletin of criminological association of Ukraine, 2024)
In the article, the author analyzed evidence of regulatory and organizational protection and anti-corruption in the prosecutor's offices of the Polish, Czech and French Republics. The main anti-corruption obligations have been clarified, which should be enforced by prosecutors in the course of their professional activities. We pay special respect to the legal status of vicious corruption, as the main subjects of the prevention of unlawful acts in the sphere of functioning of the authorities of the state. The importance of special bodies in Poland, France and the Czech Republic, which are responsible for the implementation and promotion of government anti-corruption policy, including in the law enforcement field. The important steps for the implementation of the investigation of foreign evidence into the activities of the prosecutor's office of Ukraine, in particular: 1) praise of other regulatory legal acts (either the law or the order of the Prosecutor General) h feeding robots out of corruption and avoiding conflicts of interest in the sphere. These acts may be carried out both on all subjects listed in the Law of Ukraine «On the Prevention of Corruption» dated 10/14/2014 № 1700-VII, and also on the Russian Federation system prosecutor's office; 2) increased transparency and visibility of external channels to inform about corruption in the prosecutor’s office of Ukraine, as well as properly updated information about the activities of special divisions of the prosecutor's office to prevent and prevent corruption; 3) enshrining in the Law of Ukraine «On the Prosecutor’s Office» the transfer of strict and relaxed situations that may be subject to disciplinary action, incl. how to deal with corruption cases; 4) systematically enhancing the professional training of the prosecutorial authorities to promote integrity, integrity and insight in professional activities; 5) creation of an independent system for assessing the performance of the fight against corruption in the prosecutor's office.
Keywords: corruption; foreign intelligence; law enforcement agencies; prosecutor's office; recovery; conflict of interest; anti-corruption program